(untitled) (Research, Society and Development, 2021)
In view of the challenges currently encountered in pig production, the use of additives has become one of the main nutritional strategies that help to reduce the use of antibiotics in pig diets. One of the main additives used in swine nutrition is yeast, which has products in its composition that can act as prebiotics and probiotics. With this, the objective was to carry out a literature review on the use of yeast in the diet of swine in the nursery, growth and termination phases. The variability of studies shows different results in all stages of production, since factors such as the type of yeast used, the environment that the animals are subjected to and the variability of species and microorganisms of the additives can impact on the expected results, also the type of processing that yeast is subjected can influence its mechanism of action, which can have na impact on its efficiency. Studies show that yeasts and their products improve intestinal health by modulating the microbiota, increasing the size of villi and depth of intestinal crypts, while also reducing pathogenic bacteria. Thus, it is possible to conclude through the review, that there is a need for more studies that can demonstrate the efficiency of the use of yeasts in the intestinal health of animals and zootechnical performance.